Answer:
(2x+5)(4x+3)
Step-by-step explanation:
Given the expression 8x^2 + 26x + 15
Factorize
8x^2 + 26x + 15
= 8x^2 + 6x + 20x + 15
= 2x(4x+3) + 5 (4x+3)
= (2x+5)(4x+3)
Hence the factored form of the expression is (2x+5)(4x+3)
I don’t get it but probably the scissors lol
Mr. Jones's prescription calls for 1.04 tablets per day. Based on this information, how many tablets should Mr. Jones take per day? a) 1.25 O b) 1.5 c) 10 d) 2
Answer:
12
Step-by-step explanation:
Average of A and B is 6
(A+B) /2 = 6
Multiply each side by 2
A+B = 12
average of X, Y, and Z is 16
(X+Y+Z)/3 = 16
Multiply each side by 3
(X+Y+Z) = 48
To find the average of all of them
(A+B+X+Y+Z)/5
replace A+B with 12 and X+Y+Z with 48
(12+48)/5
60/5 = 12